Pemodelan Sistem Pendukung Keputusan Pemilihan Supplier Batu Alam Dengan Algoritma Moora Pada Cv. Karisma Alam - Aldi Wahyudi Arta; Vihi Atina; Nugroho Arif Sudibyo (Infotek: Jurnal Informatika dan Teknologi, 2023)
CV. Karisma Alam is one of the largest natural cutting industries in the Candirejo area. The best supplier is one of the most important factors in production activities at this company, because it will produce good output too. Due to the large number of suppliers in this region, it is difficult for entrepreneurs to determine which supplier is the best according to the output to be produced. In the decision-making process for selecting natural stone suppliers, it is still done manually, so production activities take a long time. This decision support system assists in the decision-making process in selecting natural stone raw material suppliers at CV. Karisma Alam. In this decision support system, criteria are needed to determine the best supplier. In this study the authors used the MOORA (Multi-objective Optimization on The Basic Of Ratio Analysis) method as a decision-making method. The method used in the preparation and design uses PHP (Hypertext Preprocessor). In this study it was produced that alternative A6 was the highest alternative with a value of 0.0031. This proves that decision support systems can help and be applied to CV. Karisma Alam in selecting the best supplier.